MANAGEMENT DYSPHAGIA IN POST-STROKE PATIENTS RECOMMENDATIONS FOR INDONESIAN NURSING INTERVENTION STANDARDS: A LITERATURE REVIEW - Syahrun, Syahrun; Hany, Alfrina; Rahayu, Masruroh (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2022)
Background: Dysphagia often occurs in post-stroke patients, causing aspiration that can result in disability or death. Nurses have an essential role to play in preventing these complications as they 24/7 care for patients. However, there is no written standard of nursing care regarding specific interventions of post-stroke dysphagia in reality.Objective: The purpose of this article is to conduct a literature review of interventions that can be made in patients with post-stroke dysphagia so that it can be a recommendation for Indonesian nursing standards.Design: Electronic literature searches PubMed, EBSCO (Medline), ProQuest, and ScienceDirect databases from January 2011 to October 2020. There was sixteen studies reviewed included in this systematic study were experimental, randomized controlled trials, or systematic reviews (which are also experimental designs, randomized controlled trials). The study focused on non-invasive interventions performed on post-stroke dysphagia patients.Results: Interventions in dysphagia found, namely: The use of food thickeners against the risk of aspiration resulted in the patient's swallowing ability significantly increased by 71.9% (p <0.01); Chin down intervention combined with thickening fluid provides a solution to improve the nutritional needs of patients dysphagia post-stroke; Tongue training interventions, swallowing training and speech therapy; Tongue stretching exercises that have a positive effect on tongue motility and oromotor function in post-stroke dysphagia patients; Intervention of Tongue resistance training that increases the strength of the tongue and reduces fluid residue in the vallecular; and early screening of dysphagia by nurses using formal guidelines to manage dysphagia patients thereby reducing chest infections and mortality.Conclusion: Nurses should not diagnose dysphagia, but can identify post-stroke dysphagia to determine the interventions necessary for nutrition management, hydration, and aspiration prevention. Interventions include early dysphagia screening within 24 hours after stroke, thickening nutrition according to nutritionist recommendations, laryngeal elevation exercises, peripheral stimulation, posture regulation, and education on eating and drinking.